Potensi Sumber Daya Sargassum sp. di Kepulauan Sunda Kecil Untuk Meningkatkan Kesejahteraan Sosioekonomi Nelayan: Tinjauan Sistematis - Dermawan, Awan; Kawirian, Rizky Regina (KENANGA : Journal of Biological Sciences and Applied Biology, 2026)
Coastal communities in Indonesia’s Lesser Sunda Islands remain socioeconomically vulnerable due to seasonal variability in fisheries, climate-related pressures, limited market access, and low levels of value-added processing. Among locally abundant but underutilized marine resources, Sargassum spp. represent a promising basis for livelihood diversification because of their ecological availability and potential applications in food, pharmaceuticals, cosmetics, agriculture, and bio-based industries. This study aims to synthesize and critically assess existing scientific evidence on the distribution potential, sustainability considerations, and socioeconomic welfare implications of Sargassum resources in the Lesser Sunda Islands. A systematic literature review was conducted using peer-reviewed open-access articles indexed in Scopus and SINTA, and findings were integrated through narrative synthesis guided by the Sustainable Livelihoods Framework and a blue economy perspective. The review indicates that Sargassum occurs across multiple coastal sites in West Nusa Tenggara, that its biochemical characteristics support diverse value-added product pathways, and that welfare-relevant outcomes are most plausible when resource availability is coupled with environmentally responsible supply strategies and inclusive value-chain upgrading. By integrating ecological, technological, and livelihood evidence within a unified conceptual lens, this study provides an evidence-based foundation to inform sustainable coastal development strategies, support policy design for blue economy initiatives, and direct future research toward measurable welfare outcomes and scalable governance models. Keywords: Sargassum; alginate; coastal resource.